High strain rate persistence of the strength anomaly in the L12 intermetallic compound Ni3Si evidenced by nanoindentation testing - Merle, Benoit; Walker, Christopher C.; Zenk, Christopher; Pharr, George M. (Acta Materialia, 2025)
L12 intermetallic compounds are essential constituents of the nickel-based superalloys widely used in jet engines. They derive their exceptional high-temperature mechanical properties from the yield strength anomaly mechanism. Despite potential safety implications for collisions, e.g. bird strikes, conclusive evidence of its persistence at high strain rates has remained elusive. This is mostly due to experimental limitations, which are overcome here by combining high strain rate and high temperature testing within a single nanoindentation testing system to investigate the evolution of the strength anomaly in the L12 single-phase Ni3Si for strain rates between 0.1 and 100 s−1. High strain rates are found to extend the anomalous behavior toward higher temperatures, while the onset and peak temperatures of the strength anomaly remain largely insensitive to the applied strain rate. These experimental findings validate basic assumptions from the Paidar–Pope–Vitek (PPV) theory of its origin. In addition, high strain rates are found to increase the peak anomalous hardness, owing to the overall positive strain rate sensitivity of the L12 compound.
CRIS-Team Scopus Importer:2025-02-17
Keywords: Hardness; High strain rate; High temperature; High temperature nanoindentation; L1; Nanoindentation; Nickel base superalloys; Yield strength anomaly